Access to automatic defibrillation at airports on an example of Warsaw Chopin Airport - Witold Pawłowski; Krzysztof Goniewicz; Mariusz Goniewicz; Robert Czerski (Kazimierz Wielki University, 2017)
Sudden cardiac arrest and cessation of blood circulation is the most common cause of death of people around the world. Immediate notification of emergency services and cardiopulmonary resuscitation combined with an automatic external defibrillator (AED) increases the chances of survivors. Warsaw Chopin Airport is the only public place in Poland and the third one in Europe where a complex and integrated life saving system has been implemented in the ICC. The paper presents an analysis of the access to automatic defibrillation at airports at the Warsaw Chopin Airport